ChemInform Abstract: Total Synthesis of Hematoporphyrin and Protoporphyrin; a Conceptually New Approach. Issue 39 (5th September 2013) - Martin, Pierre; Muller, Markus; Flubacher, Dietmar; Boudier, Andreas; Spielvogel, Dirk
Abstract Review: 13 refs.